A redefinition of Paragrallomyia Hendel (Diptera: Micropezidae, Taeniapterinae) and a revision of the P. albibasis complex - Ferro, Gustavo Borges; Marshall, Stephen A. (Zootaxa, 2020)
A new diagnosis is provided for the genus Paragrallomyia, and the common and widely distributed species Paragrallomyia albibasis (Enderlein) and Paragrallomyia thiemei (Enderlein) are redefined as part of a group of 17 superficially similar Neotropical species. This group, here treated as the ‘P. albibasis complex’, includes P. albibasis, P. inpai (Albuquerque), P. teresacristinae (Albuquerque), P. thiemei, P. vulpes (Cresson) and 12 new species (P. aequorea, P. bifurcata, P. brasiliensis, P. caliensis, P. citrina, P. colombiana, P. diminuta, P. ecuadoriensis, P. nodulosa, P. pseudoalbibasis, P. quadrifurca and P. quaternaria). Paragrallomyia parens (Cresson) is newly recognized as a junior synonym of Paragrallomyia albibasis. Taeniaptera nigriceps Hennig and Taeniaptera vulpes Cresson are transferred to Paragrallomyia and 13 other species previously treated as Paragrallomyia are transferred to Poecilotylus Hennig (Grallomyia aeripennis Enderlein, Taeniaptera aliceae Albuquerque, Grallomyia dilutimacula Enderlein, Calobata latifascia Wulp, Grallomyia lauta Cresson, Grallomyia longifurca Hendel, Calobata nigritarsis Macquart, Calobata rufifacies Macquart, Grallomyia seiuncta Czerny, Tanypoda simillima Hendel, Grallomyia strigata Enderlein, Calobata tibialis Macquart, Calobata vittipennis Coquillett). Grallomyia lineata Enderlein is transferred from Taeniaptera to Poecilotylus. All named species remaining in Paragrallomyia are keyed out at least to the species complex level.